The impact of the training program in accordance with the internal and external forces in the development of some physical abilities and biomechanical variables affecting the completion of the players long jump - Abedulladeem, Ali (Journal of Physical Education, 2014)
The importance of research on the effectiveness of the long jump and the requirements of building some of its elements in accordance with the basis of new scientific, linked using the types and forms of power performance motor own, the research problem has touched researcher and through his experience as a former coach and teacher Article athletics Note that there is a decline in the level of achievement of these efficiency and lack of access to required levels and the reason is that most of the approved training curriculum focused on some of the traditional scientific bases Limited. The objectives of the research, the goal todevelop a training program based on the mutual influence of external forces (gravity, friction, center) in the internal forces contribute to the development levels of Iraqi young players effectively. The second objective is to find out the effect of exercise training program in some capacity and physical and biomechanical variables all levels of development to achieve the long horizontal of the Iraqi young players in the effectiveness of the long jump.